PP8 Paramedic views and experiences of the ethical considerations in ambulance based clinical trials: an interview study. Issue 1 (14th January 2019) - Armstrong, Stephanie; Langlois, Adele; Siriwardena, Niroshan
Abstract : Background: Prehospital ambulance based research has unique ethical considerations due to urgency, time-limitations and the locations (home, ambulance) involved. We sought to explore these issues through interviews with paramedics that have research experience. Methods: We undertook semi-structured interviews with paramedics, seeking their views and experiences of undertaking research in ambulance based clinical trials. Participants were purposively chosen because they were actively involved research and had enrolled one or more patients into a clinical trial. Participants were questioned regarding their experiences of the enrolment and consent process, and their opinions regarding the facilitators and barriers to ambulance based research. Transcripts were digitally recorded, transcribed verbatim, and analysed thematically. Results: We interviewed 15 paramedics. They ranged from newly qualified to experienced advanced paramedics. Mental capacity and consent were discussed and the time and complexity for undertaking these processes were highlighted. Participants discussed problems with completing paperwork due to the complexity of recording systems. Most highlighted paramedic training and experience as a potential barrier to research, stating that those that had gone through a university education in general seemed more open to research than those that had 'learnt on the job'. It was also felt that more information on the benefits of a trial to both patients and practice were needed from the outset to allow paramedics to make an informed decision about whether to take part in research or not. Several stated that they did additional reading around the subject before signing up. All stated that the training given prior to commencing the research was good and appropriate to each trial. Conclusions: We identified patient capacity and consent, paramedic training and experience and complexity of processes as important potential barriers to prehospital research. There is scope to improve guidance for prehospital research studies in future.